Engineers Attack the “No. One Killer” in Coal Mining: The Bureau of Mines and the Promotion of Roof Bolting, 1947–1969 - Aldrich, Mark (Technology and Culture, 2016)
In 1948 roof falls were the number one killer of coal miners in America. While the Bureau of Mines had been formed in 1910 to improve coalmine safety, it had largely focused on explosions, for which technological solutions appeared to exist. Roof falls, by contrast, were not amenable to a technical fix. Beginning in 1948, however, the Bureau discovered roof bolting, which it promoted as a safer technology that might yield dramatic benefits. The new approach spread rapidly, yet fatality rates from roof falls failed to decline for nearly two decades. This lag reflected the need for organizational learning, while companies also traded safety for productivity. Finally, only larger mines employed bolting and its impact was masked by a growth in the employment share of small companies. After 1965, as the expansion of small mines ended and organizational learning continued, fatality rates began a long decline.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM1My90ZWNoLjIwMTYuMDAyMg